Inverse Relationship between Basal Pacemaker Neuron Activity and Aversive Long-Term Memory Formation in Lymnaea stagnalis - Dong, Nancy; Feng, Zhong-Ping (Frontiers in Cellular Neuroscience, 2017)
Learning and memory formation are essential physiological functions. While quiescent neurons have long been the focus of investigations into the mechanisms of memory formation, there is increasing evidence that spontaneously active neurons also play key roles in this process and possess distinct rules of activity-dependent plasticity. In this study, we used a well-defined aversive learning model of aerial respiration in the mollusk Lymnaea stagnalis (L. stagnalis) to study the role of basal firing activity of the respiratory pacemaker neuron Right Pedal Dorsal 1 (RPeD1) as a determinant of aversive long-term memory (LTM) formation. We investigated the relationship between basal aerial respiration behavior and RPeD1 firing activity, and examined aversive LTM formation and neuronal plasticity in animals exhibiting different basal aerial respiration behavior. We report that animals with higher basal aerial respiration behavior exhibited early responses to operant conditioning and better aversive LTM formation. Early behavioral response to the conditioning procedure was associated with biphasic enhancements in the membrane potential, spontaneous firing activity and gain of firing response, with an early phase spanning the first 2 h after conditioning and a late phase that is observed at 24 h. Taken together, we provide the first evidence suggesting that lower neuronal activity at the time of learning may be correlated with better memory formation in spontaneously active neurons. Our findings provide new insights into the diversity of cellular rules of plasticity underlying memory formation.